2021
DOI: 10.3390/nu13103528
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake in Slovenian Adolescents, Adults, and the Elderly Population

Abstract: Vitamin D is involved in calcium and phosphorus metabolism, and is vital for numerous bodily functions. In the absence of sufficient UV-B light-induced skin biosynthesis, dietary intake becomes the most important source of vitamin D. In the absence of biosynthesis, the recommended dietary vitamin D intake is 10–20 µg/day. Major contributors to dietary vitamin D intake are the few foods naturally containing vitamin D (i.e., fish), enriched foods, and supplements. The present study aimed to estimate the vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…With the absence of VitD biosynthesis, sufficient dietary intake of VitD is needed, but typical intakes in most populations are rather low. For example, in Slovenia the estimated daily intake of VitD in adults is only 2.9 µg, much below the recommended intake of 20 µg/day (90)(91)(92)(93). Also in Canada, the majority of the population consumed very low amounts of VitD, and mandatory fortification of milk was, therefore, implemented (94).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the absence of VitD biosynthesis, sufficient dietary intake of VitD is needed, but typical intakes in most populations are rather low. For example, in Slovenia the estimated daily intake of VitD in adults is only 2.9 µg, much below the recommended intake of 20 µg/day (90)(91)(92)(93). Also in Canada, the majority of the population consumed very low amounts of VitD, and mandatory fortification of milk was, therefore, implemented (94).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, increased consumption of other dietary sources of vitamin D (i.e., liver, fortified margarine, eggs) is also not in line with the dietary guidelines for healthy eating. While Slovenia has not implemented mandatory fortification of foods with VitD, a very recent Slovenian study has estimated changes in dietary VitD intake in a hypothetical scenario of mandatory milk fortification with 2 μg of VitD per 100 ml ( 93 ). Study results showed a notable increase in the predicted VitD intake, but the expected intake would be still much below the recommended intake.…”
Section: Resultsmentioning
confidence: 99%
“…Folate intake distributions per age group were adjusted for individual day-to-day variation using Multiple Source Method (MSM) [58]. A similar approach was used in our previous study, investigating vitamin D intake [59]. Age, sex, and BMI were considered as covariates.…”
Section: Data Analysesmentioning
confidence: 99%
“…However, it seems that vitamin D deficiency is primarily a consequence of today's institutional lifestyle. Furthermore, due to the high incidence of vitamin D deficiency in the autumn-winter period (80% of adult and healthy Slovenes have vitamin D (25-hydroxycytamin D) insufficiency, and 40% have severe vitamin D deficiency, with an average vitamin D intake of only 3 µg/day (for adults, the reference value is set to 20 µg/day) [226,227]).…”
Section: Vitamin Dmentioning
confidence: 99%
“…The status of vitamin D was found to be lower among vegans than omnivores when serum vitamin D (i.e., 25-hydroxyvitamin D) levels were examined among vegans living at high geographical latitudes or in winter or early spring months [23,230]. However, based on data from cross-sectional studies comparing the dietary intake of vitamin D intake among vegans or omnivores [189,226,231] and the current serum vitamin D status of adults and healthy Slovenes [227] or high-performance-level Slovenian athletes [232], we may conclude that the problem of vitamin D deficiency does not originate in dietary patterns. Furthermore, researchers in Adventist Health Study 2 examined vitamin D intake relative to serum vitamin D status and could not confirm a significant difference in serum vitamin D levels between vegetarians (e.g., those who ate meat and/or fish < 1 time/month) and nonvegetarians [233].…”
Section: Vitamin Dmentioning
confidence: 99%